2016
DOI: 10.3329/bjch.v39i1.28352
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Evaluation in Full-term Newborns with Neonatal Hypoxic Ischemic Encephalopathy (HIE): A Case Control Study

Abstract: Background: Newborns with Hypoxic Ischemic Encephalopathy (HIE) are at risk of neuro-developmental disabilities. Early identification of their neuro-developmental impairments (NDI), IntroductionWith over 80% home delivery, 1 difficult and prolonged labor followed by hypoxic Ischemic encephalopathy (HIE) is common in Bangladesh. Referral of the newborns with birth related and neonatal problems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
3
3
2
Order By: Relevance
“…27 But on neurodevelopmental assessment, we found only 11.67% (7) neonate had normal development whereas development was mild, moderate and severely impaired in 10%, 33.33% and 20% neonates respectively. These findings are consistent with the findings of a study done by Banu et al 28 . In another study done by Khan et al 29 among preterm infants in Bangladesh, normal development was observed in 32%, mild impairments were found in 45%, and serious impairments were found in 23% of preterm infants.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…27 But on neurodevelopmental assessment, we found only 11.67% (7) neonate had normal development whereas development was mild, moderate and severely impaired in 10%, 33.33% and 20% neonates respectively. These findings are consistent with the findings of a study done by Banu et al 28 . In another study done by Khan et al 29 among preterm infants in Bangladesh, normal development was observed in 32%, mild impairments were found in 45%, and serious impairments were found in 23% of preterm infants.…”
Section: Resultssupporting
confidence: 94%
“…These findings are similar with a study published earlier. 28 Our study found significant association between moderate to severe impairment/death with stage III of HIE when neurodevelopmental outcome was compared with different stages of encephalopathy. The association could be attributable to the severity of the brain lesion.…”
Section: Resultsmentioning
confidence: 49%
“…In this study, on neurodevelopmental assessment, 11.67% (7) neonate had normal development whereas development was mild, moderate and severely impaired in 10% (6), 33.33% (20) and 20% (15) neonates respectively. These findings are consistent with the findings of a study done by Selina et al 21 in ICH and SSF Hospital, Mirpur, Dhaka. In another study done by Khan et al 22 among preterm infants in Bangladesh, normal development is observed in 32%, mild impairments are found in 45%, and serious impairments are found in 23% of preterm infants.…”
Section: Resultssupporting
confidence: 93%
“…This difference may be due to the adoption of different methodologies. In the study of Banu et al, 88.8% of patients had NDIs on initial assessment [14] which was higher than this study. Inclusion of only cases of moderate to severe degree of HIE may contribute to the high NDI identified in their study.…”
Section: Discussioncontrasting
confidence: 68%